TOPIK PILIHAN MAHASISWA TIONGKOK DALAM PEMBELAJARAN BIPA PROGRAM TRANSFER KREDIT DI UNY - Kusmiatun, Ari (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2016)
This study aims to describe the topics Chinese students select in the learning of Indonesian language for foreign speakers (ILFS) for the credit transfer program atYogyakarta State University (YSU). The research subjects were Chinese students joiningthe credit transfer program at YSU. The data were collected through questionnaires,interviews, and documentation. The findings show that in general Chinese students likethe topic of tourism/recreation. For the writing skill, most of them like the topic of tourism/recreation. For the reading skill, they like the topics of foods, tourism, and entertainment.For the listening and speaking skills, they like the topic of entertainment. The reasons forthe topic selection include, among others, beautiful Indonesian geography and nature,curiosity about tourist attractions in Indonesia, varieties of Indonesian foods, differencesbetween Indonesian and Chinese cultures, and the two countries’ economic development.For them, the topics they like facilitate their Indonesian language learning.